Transformasi HR di Industri Asuransi: Optimalisasi Learning & Development melalui Teknologi Digital di Era Pandemi COVID-19 - Nadhira, Siti Rahma; Heryani, Priska; Dwimarsya, Rezky; Ginting, Rico Saputra (Jurnal Manajemen dan Organisasi, 2025)
The COVID-19 pandemic has accelerated the transformation of the Human Resource (HR) function across various industries, including the insurance industry in Indonesia. One aspect that has undergone significant change is Learning & Development (L&D), which has shifted from conventional approaches to technology-based digital learning. Although numerous studies have discussed the digitalization of HR during the pandemic, research that deeply examines how HR Transformation plays a role in optimizing L&D in the post-pandemic insurance industry remains limited. This study aims to analyze the role of Human Resource Transformation (HRT) in supporting the optimization of L&D through digital technology during and after the COVID-19 pandemic. This research adopts a qualitative approach through in-depth interviews with six informants consisting of HR Managers and Operational Managers from three large insurance companies in Indonesia. The data were analyzed using thematic analysis to identify patterns of change, challenges, and strategic implications. The findings indicate that the pandemic served as a catalyst for accelerating the digitalization of L&D through the implementation of e-learning, hybrid learning, and Learning Management Systems (LMS), which enhanced learning flexibility and efficiency. However, this transformation continues to face challenges related to technology adaptation, employee engagement, and limitations in evaluating the impact of learning on business performance. This study provides empirical contributions by linking field findings with the HR Transformation framework and learning evaluation, while offering strategic implications for HR practices in the Indonesian insurance industry.